(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
تم في هذا العمل تحضير الأكسيد المشترك Al2O3/CdO بطريقة الترسيب المشترك، وتأثير الشروط (تركيز المحلول سرعة التكليس ودرجة حرارة التكليس و pH الترسيب )على قيمة المساحة السطحية النوعية للعينات المحضرة. بلغت قيمة المساحة السطحية النوعية 344m2/g عند النسبة المولية Al2O3/CdO=1-0.25 وذلك عند تحضيرها من محاليل مشبعة لأملاح الكادميوم والألمنيوم باستخدام الأمونيا المركزة كعامل مرسب عند قيمة pH=8 وبعد الترسيب والتجفيف تم تكليس العينة عند الدرجة 400oC لمدة ساعتين (بالصعق). درس تأثير نسبة الأكسيدين على عوامل البنية النسيجية وفق الشروط السابقة وذلك عند النسب: Al2O3/CdO =1-0, 1-0.125, 1-0.25, 1-0.5, 1-1,0-1 ومن معالجة بيانات الامتزاز لهذه العينات تم تعيين عوامل البنية النسيجية لها (المساحة السطحية النوعية، نصف قطر المسام المتوسط، حجم المسام الدقيق،....إلخ)، فقد وجد أن العينة AC8:1-0.25 تعطي أفضل قيمة للسطح النوعي وتحوي على نسبة أعلى من المسامية الدقيقة. In this work the mixed oxide Al2O3/CdO has been prepared using co-precipitation method. Many conditions (solution concentration, calcination temperature, rat of calcination temperature, and pH value of the precipitation ) affected the surface area of the samples. We found that the better value of specific surface area was 344m2/g when the ratio of Al2O3/CdO=1-0.25 and the saturated solutions of alumina and cadmium were used. Ammonia concentrated solution was used as precipitation agent at pH=8. The prepared samples were calcinated at 400oC for 2h. The texture properties of the samples (specific surface area pore radius, micro pore volume…etc.) were determined using adsorption data. It was found that the sample AC8: 1-0.25 has the higher value of the specific surface area and contains high content of the micro pores.